2022
DOI: 10.1186/s12875-022-01709-8
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ trust and associated factors among primary care institutions in China: a cross-sectional study

Abstract: Background Empirical evidence on patients’ trust and the factors among primary care institutions (PCIs) in China is limited. This study aimed to investigate patients’ trust and explore some associated factors among PCIs in the central region of China. Methods The data was collected through a multistage stratified sampling method with a structured self-administered questionnaire, which was distributed from January to March 2021 among 2,287 Chinese p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…This study finds a total average C-WFPTS score equal to 3.92. This result is slightly higher than the findings from China's western and central provinces ( 5 , 29 ). One possibility is that the investigated hospital/community health centers in the eastern provinces exhibit higher levels of medical skills training and technology, and medical staff provides better treatment for chronic disease patients, gaining their trust ( 5 , 16 , 47 ).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This study finds a total average C-WFPTS score equal to 3.92. This result is slightly higher than the findings from China's western and central provinces ( 5 , 29 ). One possibility is that the investigated hospital/community health centers in the eastern provinces exhibit higher levels of medical skills training and technology, and medical staff provides better treatment for chronic disease patients, gaining their trust ( 5 , 16 , 47 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Doctors may also enhance patients' confidence and vitality and lead them to actively participate in disease management, thus improving patient compliance ( 5 , 24 – 26 ). Previous studies have reported that Chinese residents express moderate trust in primary care physicians ( 27 , 28 ), and female patients are more likely to experience a high level of trust ( 29 ). Trust promotes patient satisfaction, and patients with sufficient trust in their physicians are more likely to feel satisfied with healthcare services ( 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…21 Such incentives may have served to increase NEPHSP's population coverage, but the lack of adequate quality measures could potentially compromise the accountability and enhancement of residents' trust to PHC services. 22 For over a decade, efforts have been made in China to explore and pilot innovative payment methods mainly in hospital care, such as performance-based payment. 23 Our findings suggested that innovative funding allocation mechanisms are also needed to realign PHC providers' incentives in implementing NEPHSP.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, Chinese residents, especially those with poor health, have had very little trust in the competence of primary healthcare institutions compared to tertiary hospitals [84]. Tus, patients seek health care resources directly from hospitals once they become sick [85]. Tis may be due to the gap between the service capacity of primary healthcare institutions in China and patients' diagnostic and treatment needs, which prevents patients from utilizing primary health services and forming trusting doctor-patient relationships [86].…”
Section: Discussionmentioning
confidence: 99%